Pengaruh Komposisi Media Tanam terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica chinensis L.) - KARINA SAFITRI; I PUTU DHARMA; I NYOMAN DIBIA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Effect of Plant Media Composition on Growth and Yields of Pakcoy (Brassica chinensis L.) The high rate of population growth in Indonesia has had a significant impact on total consumption and food needs. The increasing number of population also increases the need for food, however the high demand for food has not been supported by the relatively low level of food production. Planting in polybags is an alternative that can be developed in urban communities by utilizing as little land as possible to continue to be able to carry out cultivation activities so that an urban household is able to meet its own food needs. Pakcoy is one of type of vegetable that has commercial value and is popular with the public because it tastes delicious, crispy, and fresh. The potential for production and market demand for this vegetable is very large, so it needs to be utilized and managed properly and environmentally friendly, but the planting medium often occurs and plants often die due to the composition of the planting medium that does not match the plant's needs. This study aims to obtain the composition of the planting media that can provide the highest yields on the growth of Pakcoy. This study used a randomized block design (RAK) with 7 treatments for the composition of the planting media and 4 replications. The treatment level consists of KA0 (100% soil), KA1 (90% soil + 5% compost + 5% charcoal), KA2 (80% soil + 10% compost + 10% charcoal), KA3 (70% soil + 20% compost + 10% charcoal), KA4 (60% soil + 30% compost + 10% charcoal), KA5 (50% soil + 30% compost + 20% charcoal), KA6 (40% soil + 40% compost + 20 % charcoal). The results showed that the composition of the planting media significantly affected plant height and number of leaves age 21, leaf area, stem diameter, fresh weight total of the plant and dry weight total of the plant. The KA6 media treatment (40% soil + 40% compost + 20% charcoal) reaches 13.60% increase in plant height at age 21, number of leaves age 21 (14,28%), leaf area (59,74%), stem diameter (16,08%), fresh weight total (50%), dry weight total (89,56%) compared to KA0 (100% soil).